Integrating civic spirituality and civic disposition to build ethical citizen character - Mazid, Sukron; Wulansari, Atsani; Hasanah, Imroatun (Universitas Negeri Yogyakarta, 2025)
This research aims to explore and combine the concepts of civic spirituality and disposition to build ethical citizens' character. These two concepts complement each other, with civic spirituality focusing on religious values in society and civic disposition on civic attitudes that support active participation and responsibility. This research used the literature method, analysing relevant literature and theories on civic education, spirituality, and ethics. The results showed that the integration of civic spirituality and civic disposition can be a solid foundation for building the character of ethical, moral, and socially responsible citizens. This integration forms ethical citizens through religious values, such as basic morals, citizen activeness, responsibility, and norm-compliant citizenship. This concept strengthens the citizens' spiritual aspects, supports the development of a positive civic attitude, and focuses on the common good. The benefits of this research are that it offers insights for educators, policymakers, and the public in designing more comprehensive and effective civic education programs that aim to shape citizens with strong character, ethics, and morals.